Du Huo Ji Sheng Tang relieves knee osteoarthritis via suppressing NLRP3/NF-κB inflammatory signals in rats - Wenjin Chen; Jianwei Wang; Zhen Hua; Yafeng Zhang (European Journal of Inflammation, 2020)
Knee osteoarthritis (KOA) is a common chronic disease in the elderly and leads to a high rate of disability. Du Huo Ji Sheng Tang (DHJST), a Chinese traditional medicinal formula, is a classic prescription for the treatment of KOA. Here, we investigated whether DHJST could inhibit inflammation and treat KOA through suppressing NLRP3/nuclear factor (NF)-κB inflammatory signals in rats. The serum levels of interleukin (IL)-1β, IL-6, IL-10, tumor necrosis factor (TNF)-α, NLRP3, ASC, Caspase-1, p-NF-κB-P65, and p-IκBa were detected in healthy adults and patients with KOA before and after treatment. Sprague Dawley (SD) rats were divided into normal group, model group, diclofenac sodium group (5 mg/kg), DHJST high-dose group (1 g/kg), and DHJST low-dose group (0.5 g/kg). The right hind knee joint of the rats, except normal group, was injected with 4% papain (0.25 mL/kg) once every 7 days for three times. All rats were treated for 3 weeks. The swelling volume of right hind paw; five classification of inflammatory cells in synovial fluid; pathological changes of the knee-joint synovial membrane and cartilage; levels of IL-1β, IL-6, and TNF-α in serum and knee-joint synovial fluid; and the expressions of NLRP3/NF-κB inflammatory signals in the knee-joint synovial membrane were detected. The serum levels of IL-1β, IL-6, IL-10, TNF-α, NLRP3, ASC, Caspase-1, p-NF-κB-P65, and p-IκBa in KOA patients treated with DHJST were significantly decreased. The KOA rats treated with DHJST showed significant decreases in swelling volume of right hind paws; the percentage of leukocyte, lymphocyte, neutrophil, and eosinophils in synovial fluid; the levels of IL-1β, IL-6, and TNF-α in serum and knee-joint synovial fluid; and the expressions of NLRP3 ASC, Caspase-1, IL-1β, p-NF-κB-P65, and p-IκBa in the knee-joint synovial membrane, and showed an alleviation in pathological changes of the knee-joint synovial membrane and cartilage. Our data provide the first evidence that DHJST relieves KOA via suppressing NLRP3/NF-κB inflammatory signals in rats